2002
DOI: 10.1007/s00239-002-2372-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Phylogenetic Relationship of Prosimian MHC Class I Genes

Abstract: MHC class I cDNA sequences from the most divergent primate group of extant primates compared to human, the suborder Strepsirrhini (prosimians), are described. The sequences are derived from the gray mouse lemur (Microcebus murinus) and the ring-tailed lemur (Lemur catta), which are members of the malagasy Lemuriformes, as well as from the pygmy slow loris (Nycticebus pygmaeus), a prosimian from East Asia. The M. murinus sequences have been analyzed in detail. Analysis of the expression level, G/C content, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Similarly, analysis of the PBR revealed that the ‘higher’ primate MHC-E sequences are more closely related to the rodent Qa1 group than to any of the ‘lower’ primate sequences (Figure 4D). Thus, these findings indicate that the grey mouse lemur genome neither encodes a strict orthologue (with a one-to-one relationship) nor a functional homologue of MHC-E and confirm earlier data of our group that ‘higher’ and ‘lower’ primate MHC class I genes lack strict orthology [18].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, analysis of the PBR revealed that the ‘higher’ primate MHC-E sequences are more closely related to the rodent Qa1 group than to any of the ‘lower’ primate sequences (Figure 4D). Thus, these findings indicate that the grey mouse lemur genome neither encodes a strict orthologue (with a one-to-one relationship) nor a functional homologue of MHC-E and confirm earlier data of our group that ‘higher’ and ‘lower’ primate MHC class I genes lack strict orthology [18].…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, our screening of the mouse lemur BAC library for MHC class I genes also identified an unlinked genomic region that includes nine MHC class I genes. Complete sequencing of this region revealed six genes encoding functional MHC class I proteins, including putative alleles of the previously described classical class I genes of the mouse lemur, Mimu-W01 and Mimu-W04 [18] (Figure 1C). This class I gene cluster maps to another chromosome, the long arm of mouse lemur chromosome 26 (Figure 2), thus providing an additional example of a mammalian species where MHC class I and class II genes are not linked.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, all four residues of the Patr-AL motif are distributed among the MHC-E molecules of the simian primates (Figure S4). This observation, and knowledge that HLA-E is probably the oldest of the expressed MHC class I genes in simian primates (25, 26) raise the possibility that the FNSE motif first evolved at the MHC-E locus and was subsequently introduced into Patr-AL by recombination or gene conversion.…”
Section: Discussionmentioning
confidence: 98%
“…All functional lemur MHC class I genes were translocated to a different chromosome and the MHC -containing chromosome harbors only MHC class I pseudogenes [38] . Orthologous relationships between strepsirrhine and catarrhine/platyrrhine MHC class I genes are not evident [39] . In the light of the polymorphic and diverse CD94/NKG2 receptors, one would anticipate several MHC-E -like genes in lemurs.…”
Section: Polymorphic Nk Cell Receptors Of Lemursmentioning
confidence: 99%